Role of design and innovation to enhance new product development among Malaysian small and medium manufacturing enterprises (SMEs) - Nur Haizal, Mat Yaakob@Ariffin; Marzuki, Ibrahim; Mohamad Hariri, Abdullah (2021)
The role of design and innovation through NPD process can be a good platform for Malaysian SMEs to enhance their competitiveness. However, less study has been conducted to examine how the process has been implemented by SMEs. NPD process requires a proper planning and commitment from the company. Managing the NPD process by utilized design as a source of innovation will improve the quality of the product. But, many of the SMEs not utilize the potential of design and innovation as their sources to gain competitiveness. Therefore, there are gaps on how the process has been conducted by SMEs such as how they implementing, managing and who are the parties should be involved in the process. The objective of this paper is to explore the process of new product development conducted by small and medium manufacturing industries (SMEs) through design and innovation in creating added value to a product, based on an empirical study covering product, furniture, and automotive manufacturing industries in Malaysia. A mixed-method was applied consist of 450 respondents for questionnaire survey and 12 selected participants from different group's namely industrial designers marketers, and decision-makers. The results reveal the positive effects of managing design and innovations in the industries are important to improve product value and to enhance company performance through product development processes.